Aggregation thermodynamics for asphaltene precipitation. Issue 4 (9th February 2016) - Wang, Meng; Hao, Yifan; Islam, Md Rashedul; Chen, Chau‐Chyun
Abstract : Asphaltene precipitation has been a major concern for petroleum industry due to its adverse effect on upstream production, midstream transportation, and downstream refining. As a complex phenomenon involving solubility, aggregation, and clustering, asphaltene precipitation has been extensively investigated and correlated with empirical models and equations. Based on the insight regarding hierarchical structure of asphaltenes recently elucidated by Mullins, we present a thermodynamic formulation for asphaltene aggregation, the onset of asphaltene precipitation. The thermodynamic formulation accounts for asphaltene aggregation driving force as a two‐step process: (1) molecular asphaltene forming imaginary "nanocrystals", and (2) "nanocrystals" re‐dissolving as colloidal nanoaggregates. Applying UNIFAC with this thermodynamic formulation, we show semi‐quantitative predictions of asphaltene precipitation in 13 binary solvents with wide varieties of chemical structures and solvent combinations. © 2016 American Institute of Chemical Engineers AIChE J, 62: 1254–1264, 2016